Analysis of generalized multistep Adam’s methods by degenerate matrix method for ordinary differential equations - Cirulis, T.; Lietuvietis, O. (Mathematical Modelling and Analysis, 2001)
Adam’s methods in the multistep mode are considered by means of general schemes of the degenerate matrix method. The stability function for these methods is computed by the residue theory on the complex plane. Performance of uniformly and non‐uniformly distributed nodes in the standardized interval is compared. Apibendrinto Adanso metodo analizė Santrauka. Darbe nagrinėjamas daugiažingsnis Adamso metodas. Jis formuluojamas kaip atskiras atvejis bendros išsigimstančių matricų schemos. Naudojantis rezidiumų metodu ištirtas Adamso metodo stabilumas. Palygintos stabilumo sritys, kai diskretieji mazgai yra pasiskirstę tolygiai ir netolygiai. First Published Online: 14 Oct 2010